Potential for Manganese Oxide Driven Anaerobic Methane Oxidation in Sediments of a Seasonally Euxinic Coastal Basin - Robin Klomp; Anna J. Wallenius; Niels A. G. M. van Helmond; Wytze K. Lenstra; Olga M. Żygadłowska; Mike S. M. Jetten; Caroline P. Slomp (Estuaries and Coasts, 2026)
Methane (CH 4 ) is a strong greenhouse gas that, in marine sediments, is produced via methanogenesis and removed via oxidation with electron acceptors such as oxygen, sulfate and metal oxides . This study assesses the potential for manganese driven anaerobic oxidation of methane (Mn-AOM) in rapidly accumulating sediments in a seasonally euxinic coastal marine basin (Scharendijke basin, Lake Grevelingen, the Netherlands). Geochemical sediment and porewater profiles demonstrate that, at the study site, Mn oxides are buried in the methanic zone. Sediment incubations amended with 13 C-CH 4 and various Mn forms indicate that the Mn oxide minerals birnessite, pyrolusite and manganite can enhance CH 4 oxidation, whereas ligand bound dissolved Mn(III) does not. This is attributed to either direct Mn-AOM, where Mn oxides act as the electron acceptor, and/or indirect Mn-driven AOM via cryptic sulfur cycling. Results of 16S rRNA gene amplicon sequencing of the incubated sediment point towards a likely role for anaerobic methanotrophic archaea of the clades ANME-2ab and ANME-3 in direct and indirect Mn-driven AOM, respectively. An increase in relative abundance of the methanogen Methanosarcina in several of the incubations suggests that these versatile methanogens benefit from Mn oxide reduction. This study demonstrates potential for Mn-driven AOM in sediments from a eutrophic, seasonally euxinic coastal basin, and expands the range of electron acceptors involved in CH 4 removal in such systems.